2022
DOI: 10.4236/jmmce.2022.105027
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Composite Based on Natural Rubber Reinforced with Short Fibers of the <i>Triumfetta cordifolia/Saccharum officinarum</i> L.: Performance Evaluation

Abstract: This article contributes to the development of the new class of fully biodegradable "green" composites by combining fibers (natural/bio) with biodegradable resin. The vegetable fibers (Triumfetta cordifolia and sugarcane bagasse) treated with NaOH and bleached were incorporated into a natural rubber matrix. The influence of the fiber ratio on the physical properties, tensile strength and surface hardness of the hybrid composites was analyzed. The results show that the addition of fibers in the natural rubber m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Irawan et al [15] conducted thermal and mechanical characterization of hybrid composites made from rattan strips and glass fiber reinforced in epoxy resin for automotive applications. Njom et al [16] introduced "green" composites which is a combination of vegetable fibers and natural rubber matrix to improve water absorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Irawan et al [15] conducted thermal and mechanical characterization of hybrid composites made from rattan strips and glass fiber reinforced in epoxy resin for automotive applications. Njom et al [16] introduced "green" composites which is a combination of vegetable fibers and natural rubber matrix to improve water absorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Grosser et al [16] showed that a polylactide (PLA) matrix reinforced with unidirectionally arranged TC bers exhibited mechanical properties comparable to those of PLA/hemp composite. Njom et al [17] developed green hybrid composites by combining bleached TC and bagasse bers with a natural rubber (NR) matrix. The authors showed that the combination of two bers improves the physical and mechanical properties of the NR matrix and these hybrid composites are good candidates for engineering applications.…”
Section: Introductionmentioning
confidence: 99%